Detection of 13 mycotoxins in feed using modified QuEChERS with dispersive magnetic materials and UHPLC–MS/MS. Issue 3 (11th December 2017) - Qian, Mingrong; Yang, Hua; Li, Zuguang; Liu, Yanping; Wang, Jianmei; Wu, Huizhen; Ji, Xiaofeng; Xu, Jie
Abstract: An analytical method for the simultaneous determination of 13 mycotoxins in feed by magnetic dispersive solid‐phase extraction combined with ultra‐high performance liquid chromatography and tandem mass spectrometry was developed. The samples were extracted with acetonitrile/water (80:20, v/v, containing 3% acetic acid), and separated by centrifugation after salting‐out, and then treated with magnetic adsorbents to remove interferences. The separation of target mycotoxins was performed on an ACQUITY UPLC HSS T3 column using a mobile phase consisting of 1 mmol/L ammonium acetate with 0.1% formic acid and methanol by gradient elution. Good linearities for the 13 mycotoxins were achieved with correlation coefficients over 0.99, and the recoveries of mycotoxins were in the range of 89.3–112.6% at spiking at levels of 5, 20, and 100 μg/kg, with relative standard deviations of 0.9–10.4%. Based on the functional magnetic materials (MDN@Fe3 O4, PSA@Fe3 O4, ZrO2@ Fe3 O4 ) applied in dispersive solid‐phase extraction, the pretreatment process is more convenient and it is beneficial to reduce the experimental cost by reusing the recycled magnetic materials. It is a simple, rapid, and environmentally friendly analytical method for the determination of mycotoxins in feed.